Veterinary medical student perceptions of companion animal primary care as a career choice over an academic year - Nappier, Michael T.; Corrigan, Virginia K.; Borowski, Shelby; Lusk, Danielle (Frontiers in Veterinary Science, 2022)
Despite companion animal primary care being the most common career choice for veterinarians, relatively little is known about students’ perception of this career choice. In this study, the authors examined students’ (233 at Time 1 and 119 at Time 2) perceptions of careers in companion animal primary care and whether perceptions changed over the course of an academic year or differed by year in veterinary school. The study was conducted by an online questionnaire sent to the student email listserv and the results analyzed by Mixed ANOVAs for each perception outcome. The study concluded that a majority of veterinary students have companion animal primary care as their preferred career choice and have a positive perception of it as a career choice. This positive perception increased over the course of an academic year, but did not differ significantly by year in school. First year students had a decrease in perception of level of training over time. This study sets a baseline for students’ perceptions of companion animal primary care as a career choice at one college of veterinary medicine.